The Interplay of Work Experience and Educational Diversity in Shaping Entrepreneurial Intentions: A Qualitative Synthesis - Seger Santoso; Benardi Benardi (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores how the interplay between work experience and educational diversity influences entrepreneurial intentions. Synthesizing findings from recent empirical studies, the review highlights how practical experience enhances entrepreneurial self-efficacy and opportunity recognition, while diverse educational backgrounds promote cognitive flexibility and skill variety. The analysis reveals that the dynamic interaction of these factors more effectively fosters entrepreneurial intentions than either factor alone. Mediating variables such as self-efficacy, skill complementarity, and exposure to entrepreneurial environments emerge as critical mechanisms. The study contributes a holistic perspective on entrepreneurial intention formation and offers implications for education, career development, and entrepreneurship policy